MENINGKATKAN HASIL BELAJAR TARI TRADISIONAL MELALUI STRATEGI COOPERATIVE LEARNING DI KELAS X IPA 3 DI SMA NEGERI 1 KOTA SOLOK - Jasmi Fanella; Yuliasma Yuliasma; Zora Iriani (FBS Universitas Negeri Padang, 2018)
AbstractThis article aimed to explain and describe the Improvement of Student Learning Outcomes of Traditional Dance by using the Cooperative Learning Method in class X IPA 3 SMA Negeri 1 Solok. The type of this research was Classroom Action Research. The flow of this study was conducted in 2 cycles, namely cycle I and cycle II. The research instrument was obtained from written tests and practice tests. The types of data in this research were primary data and secondary data. Data collection techniques were done through written tests and practice tests, document studies and observations. The results of this study showed that the use of Cooperative Learning methods in learning art and culture, especially dance in class X IPA 3 SMA Negeri 1Solok could improve the learning outcomes. In the first cycle, there was no significant increase in student learning outcomes. After continuing in the second cycle using the Cooperative Learning method, it was found that that student learning outcomes increased. This was proved by the learning outcomes of class X IPA 3 students in the first cycle of student learning outcomes with an average of 76.04 and cycle II with an average score of 83.84. Thus, there has been an improvement in learning outcomes of dance art using Cooperative Learning methods and targets has been achieved successfully as well.Keywords: Learning Outcomes, Traditional Dance, Cooperative Learning